Environmental Crime Enforcement in Indonesia: Ultimum and Primum Remedium Perspectives - Valerie Zhou (PDIH Untag Semarang, 2025)
Environmental law enforcement in Indonesia continues to face significant challenges despite severe ecological and socio-economic impacts caused by environmental degradation. A key issue is the tendency to treat criminal law as primum remedium, leading to excessive criminalisation, whereas environmental law principles emphasise criminal sanctions as ultimum remedium. This imbalance weakens the role of administrative and civil instruments that are essential for achieving effective environmental restoration. This study aims to critically analyse the appropriate positioning of ultimum remedium and primum remedium within Indonesia’s environmental law enforcement framework and to identify the challenges encountered by law enforcement officials. Using a normative juridical method, it adopts a conceptual and legislative approach while examining legal doctrines and selected court decisions on environmental crimes. The findings indicate that although criminal sanctions remain crucial as deterrents, prioritising them as the main enforcement tool may undermine more substantive efforts toward ecological recovery. Strengthening administrative and civil mechanisms offers a more proportional and sustainable approach. The study concludes that Indonesia must clarify parameters for applying criminal sanctions and enhance synergy across legal instruments to realise effective environmental protection and ecological justice.